Benchmarking of numerical models for wave overtopping at dikes with shallow mildly sloping foreshores: Accuracy versus speed. (August 2020) - Lashley, Christopher H.; Zanuttigh, Barbara; Bricker, Jeremy D.; van der Meer, Jentsje; Altomare, Corrado; Suzuki, Tomohiro; Roeber, Volker; Oosterlo, Patrick
Abstract: Practitioners often employ diverse, though not always thoroughly validated, numerical models to directly or indirectly estimate wave overtopping ( q ) at sloping structures. These models, broadly classified as either phase-resolving or phase-averaged, each have strengths and limitations owing to the physical schematization of processes within them. Models which resolve the vertical flow structure or the full wave spectrum (i.e. sea-swell (SS) and infragravity (IG) waves) are considered more accurate, but more computationally demanding than those with approximations. Here, we assess the speed-accuracy trade-off of six well-known models for estimating q, under shallow foreshore conditions. The results demonstrate that: i) q is underestimated by an order of magnitude when IG waves are neglected; ii) using more computationally-demanding models does not guarantee improved accuracy; and iii) with empirical corrections to incorporate IG waves, phase-averaged models like SWAN can perform on par, if not better than, phase-resolving models but with far less computational effort. Highlights: Overtopping is an order of magnitude lower when infragravity waves are neglected. Using more computationally-demanding models does not guarantee improved accuracy. Despite well-modelled infragravity waves, XBeach Surfbeat underestimates overtopping. With empirical corrections, SWAN can account for infragravity waves. Phase-averaged models can perform on par, if not better, than phase-resolving models.